KARAKTERISTIK MINUMAN KOMBUCHA TEMULAWAK (Curcuma xanthorrhiza Roxb) HASIL FERMENTASI PADA BERBAGAI KONSENTRASI EKSTRAK DAN LAMA INKUBASI: Characteristics of Temulawak Kombucha Drink (Curcuma xanthorrhiza Roxb) Fermentation Product at Various Extract Concentrations And Incubation Lengths - Mukhammad Fauzi; Soni Sisbudi Harsono; Yanis Nurana (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2023)
In the modern era, the utilization of curcuma has not utilized optimally, which is normally processed into jamu (traditional beverage). Curcuma practically can be processed into a fermented drink which is called kombucha. The research purpose was to discover the effect of curcuma extract concentration and fermentation period the characteristic of curcuma kombucha. The research applied two-factor Randomized Block Design (RBD) are the curcuma extract concentration (5%, 10%, and 15%) of the total used water and the fermentation period (6, 9, 12, and 15 days). The best treatment for making curcuma extract kombucha was the sample 10% curcuma extract and 9-day fermentation, resulting in curcuma extract kombucha characterized by the total dissolved solids of 11.22 Brix; viscosity 0.97 cP; brightness (*L) 57.24; pH 3.32; total acid 0.73%; antioxidant activity 74.82%; favorite organoleptic color 5.77 (like); fragrance preference 3.57 (neutral); taste preference 5.10 (slightly like) and overall 5.50 (like).